Variabilnost srčne frekvence pri športnikih in njena povezava z maksimalno aerobno kapaciteto - Vičič, Peter (Medicinski razgledi, 2011)
Backgrounds. Heart rate variabi1ity increases with increased vagal effect. Compared to sedentary individuals, athletes have an increased vagal tone. Their resting heart rate decreases and heart rate variability increases. The aim of the study was to determine whether heart rate variability correlates with maximal aerobic capacity in a random population of athletes, and to establish any differences in heart rate variability between male and female athletes. Methods. The study included a sample of 63 athletes ofboth genders from different sporting disciplines. After recording alO-minute ECG at rest inthe supine position, they underwent a continuous graded stress test on a treadmill to determine their maximal aerobic capacity. The heart rate variability components and their relationships were then compared to maximal aerobic capacity. In order to determine the differences in heart rate variability between the high capacity and low capacity groups, and between themale and female groups, t-test for normally distributed and ANOVO test for non-normally distributed variables were used. The Pearson method for normally distributed variables and the Spearman method for non-normally distributed variables were used to determine the correlation coefficients between heart rate variability and maximal aerobic capacity. The P-value of < 0.05 was considered statistically significant. Results. No significant differences werefound in heart rate variability between the lower and higher maximal aerobic capacity groups or between the males and females. There was also no correlation between heart rate variability and maximal aerobic capacity in ourgroup of athletes. Conclusions. The connection between maximal aerobic capacity and heart rate variability in highly trained individuals is obviouslynot as direct as in the non-athletic population. (Abstract truncated at 2000 characters)
Keywords: Heart Rate; Srčna frekvenca; Sports; Elektrokardiografija; Electrocardiography; Športi; Exercise Test; Kisik, poraba; Obremenitveni test; Oxygen Consumption; Sex Factors; Spolni faktorji; Analiza variance; Analysis Of Variance; variabilnost; športniki